PERBANDINGAN METODA DIFFERENTIAL EVOLUTIONARY ALGORITHM DENGAN LAGRANGE MULTIPLIER PADA OPTIMISASI ECONOMIC DISPATCH - Dinzi, Riswan; Siregar, Yulianta; Siregar, Melinda Zubara (Universitas Nusa Cendana, 2023)
In power plant operation, the highest cost is the cost of fuel, so it is necessary to optimize the Economic Dispatch (ED), which aims to analyze the economic operation of the thermal generator by performing simulation calculations to obtain optimal power and more economical generator operating costs. In this thesis, ED optimization is carried out using the Differential Evolutionary Algorithm (DEA) method at the Pangkalan Susu PLTU. The DEA method is validated with the Lagrange Multiplier method. DEA simulation results are not much different from the Lagrange Multiplier method. The results of the fuel cost comparison using the DEA method are more economical than the fuel costs for the Pangkalan Susu PLTU. In this thesis, the author takes a sample load data of 4 units of Pangkalan Susu PLTU in February 2021. The simulation results of the DEA method for load data for February 2021 produce an average cost savings of 3,111.64 US/h with a saving percentage of 14, 01%. The lowest average fee is on February 1, 2021, for 17,108.68 US/d, while the highest average fee is on February 21, 2021, for 20,478.61 US/h..